Vibration test and parametric study of concrete flooring system towards human comfort - Mohd Azaman, Nur 'Amirah (2019)
In recent years, there has been an increase in floor vibration problems of structures such as residential and commercial buildings. Vibration is defined as one of the serviceability issues related to the human comfort. Human activities is the one of the factor vibration in buildings and vibrations exceeding the recommended level. People could feel sick and not comfortable if the floor vibrates at the resonant frequency of human body. Hence, this research focused on the dynamic behaviour on first floor of a two-storey Madrasah Tahfiz building. Vibration tests and finite element were used to determine dynamic behaviour with regards to natural frequency,